The potential effects of climate change on amphibian distribution, range fragmentation and turnover in China - Duan,Ren-Yan; Kong,Xiao-Quan; Huang,Min-Yi; Varela,Sara; Ji,Xiang (PeerJ PrePrints, 2016)
Many studies predict that climate change will cause species movement and turnover, but few studies have considered the effect of climate change on range fragmentation for current species and/or populations. We used MaxEnt to predict suitable habitat, fragmentation and turnover for 134 amphibian species in China under 40 future climate change scenarios spanning four pathways (RCP2.6, RCP4.5, RCP6 and RCP8.5) and two time periods (the 2050s and 2070s). Our results show that climate change will cause a major shift in the spatial patterns of amphibian diversity. Suitable habitats for over 90% of species will be located in the north of the current range, for over 95% of species in higher altitudes, and for over 75% of species in the west of the current range. The distributions of species predicted to move westwards, southwards and to higher altitudes will contract, while the ranges of the species not showing these trends will expand. Amphibians will lose 20% of their original ranges on average; the distribution outside current ranges will increase by 15%. Climate change will likely modify the spatial configuration of climatically suitable areas. Changes in area and fragmentation of climatically suitable patches are related, which means that species may be simultaneously affected by different stressors as a consequence of climate change.
Keywords: Climate impacts; MaxEnt; Distribution; Fragmentation; Amphibians; Dispersal; Turnover; Range shifts